Synthesis and evaluation of antioxidant, antimicrobial and antifungal effect of [(5-hydroxymethyl-1H-imidazole-4-il)thio] acetic acids - V. O. Chornous; A. O. Palamar; I. M. Yaremiy; N. D. Yakovychuk; M. V. Vovk (Zaporožskij Medicinskij Žurnal)
By reduction of available [(1-aryl-5-formylimidazole-4-il)thio] acetic acids with sodium borohydrideinaqueous solution in presence of 20% solution of sodium hydroxide [(5-hydroxymethyl-1H-imidazole-4-il)thio] acetic acids were synthesized. Their structure was proved by results of measurements of IR-, NMR 1H and chromatography-mass pectra. Primary screening of antioxidant properties showed that in in vitro experiments all of the studied compounds are active in range of concentrations between10-1-10-3mole/l, and the highest antioxidant effect is shown by {[5-hydroxymethyl-1-(3-methylphenyl)-1Н-imidazole-4-il]thio} acetic acid in concentration 10-3 М, which is credibly the same as the effect of thiotriazolin in the same concentration. It was found that the synthesized compounds show moderate antimicrobial and antifungal effect.